Gene therapy for primary immunode!ciency diseases: where are we now? (Bangladesh Medical Journal, 2016)
In 1950s, double-stranded deoxyribonucleic acid (DNA) had been identified as the biochemical basis of heredity and gene had been shown to be a segment of DNA. Accordingly, vast majority of hereditary disorders involve changes, i.e. mutations in specific genes. Can medical treatment leading to genetic cure of these hereditary disorders possible? The answer is yes as the initial thoughts of Gene therapy have been transformed into reality in recent times. Gene therapy is the application of various technologies including Recombinant DNA Technology for introduction of a relevant functional gene, i.e. exogenous DNA, into a cell to achieve therapeutic effects for genetic disorders. Since 1990, gene therapy has become standard treatment for a number of primary immunodeficiency diseases (PIDs) such as adenosine deaminase deficiency form of severe combined immunodeficiency (ADA-SCID), SCID-X1, Wiskott-Aldrich syndrome (WAS), chronic granulomatous disease (CGD) and others. As we eagerly wait until the results of ongoing further clinical trials are available, updated accounts of the status of Gene Therapy for selective PIDs are presented in this review article.Bangladesh Med J. 2015 Sep; 44 (3): 160-164